2018
DOI: 10.1002/cphc.201700339
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Computational Enzymatic Reactivity Based on Geometry Optimisation

Abstract: Enzymes play a biologically essential role in performing and controlling an important share of the chemical processes occurring in life. However, despite their critical role in nature, attaining a clear understanding of the way an enzyme acts is still cumbersome. Computational enzymology is playing an increasingly important role in this field of research. It allows the elucidation of a complete and detailed mechanism of an enzymatic reaction, including the characterization of reaction intermediates and transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 145 publications
(175 reference statements)
1
28
0
Order By: Relevance
“…Finally, it is important to discuss the use of the X-ray conformation (the most abundant conformation) for the determination of the chemical mechanism and barrier height. A very large body of studies 19,[57][58][59][60][61][62][63] shows that a correct X-ray conformation almost always provides barrier heights in agreement with experiments, and chemical mechanisms that are widely accepted to also be correct. This is particularly true for Xray structures co-crystallized with a substrate/transition state analogue.…”
Section: The Origin Of the Barrier Uctuations In Each Reaction Mechamentioning
confidence: 80%
“…Finally, it is important to discuss the use of the X-ray conformation (the most abundant conformation) for the determination of the chemical mechanism and barrier height. A very large body of studies 19,[57][58][59][60][61][62][63] shows that a correct X-ray conformation almost always provides barrier heights in agreement with experiments, and chemical mechanisms that are widely accepted to also be correct. This is particularly true for Xray structures co-crystallized with a substrate/transition state analogue.…”
Section: The Origin Of the Barrier Uctuations In Each Reaction Mechamentioning
confidence: 80%
“…The ZPE, thermal, and entropic energy corrections were calculated at 310.15 K and 1.0 bar. A more detailed overview about the methodology that was followed in this study can be found in the literature …”
Section: Methodsmentioning
confidence: 99%
“…A more detailed overview about the methodology that was followed in this study can be found in the literature. [44] The final energies of minima in all steps were calculated using a more complete basis set, 6-311 + + G(2df,pd) in the HL layer. The activation and reaction free energies were calculated through the difference between the Gibbs free energy of TS and reactant, or product and reactant, respectively.…”
Section: The Choice Of the Hlmentioning
confidence: 99%
“…The user can also save his/her own template and include it in the dropdown menu to have it accessible when future input files will be prepared. For example, in ONIOM calculations, the user can easily interchange between mechanical and electrostatic embedding type of calculations, which only differ in a single keyword (for more details see Supporting Information) …”
Section: The Molup Pluginmentioning
confidence: 99%